COMPARATIVE ACCOUNT OF GROWTH RATE OF BODY PARTS WITH TOTAL LENGTH IN RITA PAVIMENTATA (GUNTHER) - QURESHI, T. A.; TIWARI, V. K. (Journal of Indian Fisheries Association, 2015)
The paper deals with sex-wise growth rate of different body parts inrelation to total length in Rita pavimentata (Gunther). Growth rates calculatedon pooled dat~ by using the common regression coefficient 'b' reveals isometricand homogeneous nature in sexes.Keywords : Rita, isometric, regression, Narmada, India